Income inequality in Central America, Dominican Republic and Mexico : assessing the importance of individual and household characteristics - Hammill, Matthew (UN MexicoMX, 2005)
Investigates the relationship between individual and household characteristics and income inequality in Central America, the Dominican Republic and Mexico from 1990 to 2002.